Yield of tomato (Solanum lycopersicum) as a function of potassium phosphite as foliar fertilizer - Mayén-Villa, Rosa Inés; Morales-Rosales, Edgar Jesús; Morales-Morales, Edgar Javier; López-Sandoval, José Antonio (Ecosistemas y Recursos Agropecuarios, 2023)
Tomato (Solanum lycopersicum) is consumed worldwide as it is rich in vitamins and mineral salts. QfosfiK® is a biostimulant that increases yield and improves fruit quality in different crops. The objective of the research was to evaluate the effect of foliar application of potassium phosphite on the growth and yield of tomato cultivars Paipai and Cid. The experiment was conducted under greenhouse conditions at the Faculty of Agricultural Sciences, during 2019 on a vertisol soil, in a randomized block design with 10 treatments and 4 replications. The treatments applied arose from the factorial arrangement of the two tomato cultivars and five concentrations of potassium phosphite (0, 1.2, 1.5, 1.5, 1.8 and 2.1 L ha−1) prorated at transplanting, vegetative stage and beginning of the reproductive stage. Leaf number, leaf area index, net assimilation rate, berry yield and morphological components: number of clusters and fruit were evaluated. The cultivar Cid had the best yield due to the highest number of leaves, leaf area index, net assimilation rate and number of bunches plant−1. Regarding the doses, when 1.2 L ha−1 was added, yield was optimized. The cultivar × dose interaction revealed that the highest fruit yield was achieved by Cid (3.18 kg plant−1) when 1.2 L ha−1 of product was added, while Paipai with 1.5 L ha−1 produced 2.74 kg plant−1.